Telling Sounds Tracing Music History in Digital Media Archives - Berner, Elias (Hollitzer Verlag, 2023)
How are music and sound involved in the creation of audiovisual documents? What kind of quantitative and qualitative research permits the examination of music and, more generally, sound for Austrian (music) history on the basis of digitized audiovisual sources? These questions were approached in the interdisciplinary Digital Humanities project "Telling Sounds" at the Universität für Musik und darstellende Kunst in Vienna.This volume consists of various case studies conducted by the members of the team. The project's main task was the conception and development of a Digital Humanities research tool: LAMA - Linked Annotations for Media Analysis. It was designed for the purpose of using machine-readable open data to annotate and link the ways in which music has been used and contextualized in different audio and audiovisual media texts in different times throughout Austrian history. Each of the case studies is dedicated to different genres of music, media texts, and events or timespans in history.Contributions by Aylin Basaran Elias Berner Paul Gulewycz Birgit Haberpeuntner Julia Jaklin Birgit Michlmayr Peter Provaznik Cornelia Szabó-Knotik Meike Wilfing-Albrecht